Kajian Input Energi pada Budidaya Padi Metode System of Rice Intensification - Bambang Purwantana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
System of Rice Intensification (SRI) is a rice cultivation method that intensively control and manage macro and micro nutrients as well as irrigation. This paper quantifies and compares the energy uses of SRI and conventional rice cultiva- tion systems. The study was conducted at some SRI’s experimental plots in the districts of Sleman, Kulonprogo, and Bantul, the province of Yogyakarta. The calculation of the energy was based on the farmers’ work schedule, the time required for each operation, the number of laborers, machines, tools, fuel, and all materials and inputs used. The result shows that SRI method consumed 35% less energy to conventional rice cultivation. Energy inputs from seed, water, fertilizer and pesticide were significantly reduces. However, there was higher input of human energy due to compost- ing, land preparation and weeding operations. The specific energy of SRI method was 1.96 MJ ha-1 lower than conven- tional method of 4.43 MJ ha-1. In the SRI method, 56.2 % of energy consumed was classified as direct energy and 43.8% was indirect energy. The SRI method used 61.9 % of renewable energy and 38.1 % of non-renewable energy. The working efficiency in composting and weeding operations should be improved in perspective of machine and tools to reduce the use of human energy.ABSTRAKSystem of Rice Intensification (SRI), merupakan suatu metode budidaya padi secara intensif dengan pengendalian unsur-unsur hara makro dan mikro disertai pengendalian dan pengaturan kebutuhan air. Penelitian ini bertujuan untuk menganalisis penggunaan energi dan mengidentifikasi kemungkinan penghematan energi pada budidaya padi SRI. Pe- nelitian dilakukan di Kabupaten Sleman, Kulonprogo, dan Bantul, Propinsi Daerah Istimewa Yogyakarta. Pengamatan dilakukan pada plot-plot percobaan budidaya padi SRI dengan melakukan audit seluruh input energi selama proses budidaya dan dikomparasikan dengan input energi pada budidaya padi cara konvensional. Hasil penelitian menunjuk- kan bahwa budidaya padi metode SRI menggunakan input energi 35 % lebih kecil daripada input energi pada budidaya padi konvensional. Input energi dari benih, pupuk dan pestisida kimia serta air irigasi berkurang sangat signifikan, meskipun terdapat kenaikan input energi manusia untuk pekerjaan pembuatan kompos, penyiapan lahan dan penyian- gan. Metode SRI termasuk kategori budidaya kurang padat energi dengan energi spesifik 1,96 MJ kg-1, lebih rendah dari metode konvensional yaitu 4,43 MJ kg-1. Berdasar klasifikasi energinya, metode SRI menggunakan 56,2 % jenis energi langsung dan 43,8 % sumber energi tak langsung, 61,9 % energi terbarukan dan 38,1 % energi tak terbarukan. Efisiensi penggunaan alat dan mesin pada pekerjaan pembuatan kompos dan obat serta pemeliharaan tanaman perlu dikembangkan untuk mengurangi kebutuhan tenaga manusia.